Two novel BTD mutations causing profound biotinidase deficiency in a Chinese patient. Issue 2 (16th January 2021) - Geng, Jia; Sun, Yi; Zhao, Yi; Xiong, Wenyu; Zhong, Mingjun; Zhang, Yajuan; Zhao, Qiuling; Bao, Zhongwei; Cheng, Jing; Lu, Yu; Yuan, Huijun
Abstract: Background: Biotinidase deficiency (OMIM 253260) is an autosomal recessively inherited disorder affecting about 1/60, 000 people worldwide. The absence or deficiency of biotinidase impairs free biotin recycling and affects biotin‐dependent carboxylase functions. Methods: A Chinese patient with spontaneous recurrent epilepsy, an eczema‐like rash, hair loss, hypotonia, and hearing loss began at three months of age. Her biotinidase activity was 1.0 nmol/ml/min, 9.5% of the mean control activity, which confirmed profound biotinidase deficiency. Results: Compound heterozygous for c.250‐1G > C and c.878dupT variants in the BTD gene were identified in this patient. These two variants were novel and absent in the population matched controls and any databases. Conclusions: This study expanded the mutation spectrum of alterations of the BTD gene. Our patient also emphasized the critical role of biotinidase activity measurement combined with mutation analysis in early diagnosis of biotinidase deficiency. Abstract : In this paper, we report two novel mutations of the BTD gene identified in a Chinese patient diagnosed with biotinidase deficiency (BTD). By next generation sequencing (NGS), we identified compound heterozygous c.250‐1G > C and c.878dupT mutations of the BTD gene in this patient which were absent in 7, 205 controls with Chinese background. After biotin treatment, most of her symptoms disappeared, except the hearing loss. Our study expands the mutation spectrum of BTD and emphasize genetic test plays a key role in early diagnosis.